The mental game of tennis: A scoping review and the introduction of the resilience racket model - Konstantinou, G. N.; Kloiber, S.; Blumberger, D. M. (Sports, 2025)
This review examines the relationship between tennis participation and mental health, highlighting both the psychological benefits and challenges associated with the sport. Using a retrospective, citation-based methodology, peer-reviewed studies published in English, French, and Greek between 2000 and March 2025 were included. The findings indicate that tennis participation is associated with reductions in depressive and anxiety symptoms, improved self-confidence, and enhanced resilience. However, competitive tennis also presents significant psychological demands, including elevated stress levels and susceptibility to maladaptive coping behaviors. To address these complexities, this review introduces the Resilience Racket Model, a conceptual framework representing the integration of physical readiness, psychological resilience, and systemic support. The model uses the metaphor of a tennis racket: the handle reflects foundational physical skills; the strings represent resilience components; the frame denotes environmental and organizational support; and the sweet spot signifies the optimal balance between physical and mental readiness. The review also highlights the effectiveness of psychological interventions, such as cognitive-behavioral therapy and mindfulness, in supporting athlete well-being. These findings advocate for a holistic approach to athlete development, emphasizing parity between mental health and physical training, and call for further research into tailored, sport-specific mental health interventions in tennis.